PERCEPTION OF ACADEMIC EXAMINATION STRESS: EFFECTS ON SERUM LEPTIN, CORTISOL, APPETITE AND PERFORMANCE - Inam, Qurrat -ul-Aen; Shireen, Erum; Haider, Saida; Haleem, Darakhshan Jabeen (Journal of Ayub Medical College Abbottabad, 2011)
Background: Examination stress is a psychological stress that activate hypothalamic-pituitary adrenocortical (HPA) axis to increase circulating levels of glucocorticoids. The fat derived hormone leptin is also released in response to stress-inducing condition. To workout the role of leptin and cortisol in response to perceived levels of examination stress and their effects on academic performance. The present study was designed to monitor the relationship of self reported perceived levels of examination stress on serum levels of cortisol and leptin in female students going to appear in university examination. Methods: Fifty-six female undergraduate students participated in the study. Examination stress, appetite levels were assessed by a questionnaire and blood samples were collected one hour before appearing in the examination. Performance was evaluated from the marks obtained in that particular examination. Results: Serum cortisol levels increased with an increase in the intensity of perceived examination stress. Serum leptin levels increased only in the group under moderate stress while increases in mild and severe stress group were not significant. Mild to moderate stress enhanced performance but severe stress decreased it. Conclusions: The present study shows an inverted U-shaped relationship between self reported different levels of perceived examination stress and academic performance. Keywords: Academic Stress, Cortisol, Leptin, Appetite, Performance